1996
DOI: 10.1126/science.273.5278.1058
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the Methanogenic Archaeon, Methanococcus jannaschii

Abstract: The complete 1.66-megabase pair genome sequence of an autotrophic archaeon, Methanococcus jannaschii, and its 58- and 16-kilobase pair extrachromosomal elements have been determined by whole-genome random sequencing. A total of 1738 predicted protein-coding genes were identified; however, only a minority of these (38 percent) could be assigned a putative cellular role with high confidence. Although the majority of genes related to energy production, cell division, and metabolism in M. jannaschii are most simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
1,531
3
5

Year Published

1997
1997
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,273 publications
(1,577 citation statements)
references
References 63 publications
38
1,531
3
5
Order By: Relevance
“…The 3Ј end of ORF1 codes for a 57-aa partial sequence too short to be significantly analyzed. ORF2 encodes a 404-aa protein which exhibits high similarities to archaeal adenosylhomocysteine hydrolases: 54% identity with the enzyme from Sulfolobus solfataricus (36) and 57% with that from M. jannaschii (7).…”
Section: Resultsmentioning
confidence: 99%
“…The 3Ј end of ORF1 codes for a 57-aa partial sequence too short to be significantly analyzed. ORF2 encodes a 404-aa protein which exhibits high similarities to archaeal adenosylhomocysteine hydrolases: 54% identity with the enzyme from Sulfolobus solfataricus (36) and 57% with that from M. jannaschii (7).…”
Section: Resultsmentioning
confidence: 99%
“…Sketched phylogenetic tree, according to the present knowledge (Woese et al+, 1990;Pace, 1997), showing distribution of the tRNA Sec secondary structure models+ The tRNA Sec secondary structure of the Archae M. jannaschii (sequence from Bult et al+, 1996) folds into the 9/4 model+ Dotted line represents a putative U-A base pair+ The tRNA Sec secondary structure of the hyperthermophilic bacterium A. aeolicus (sequence from Deckert et al+, 1998) folds into the 8/5 model, as do the other bacterial tRNAs Sec + An alternate 2D structure can be proposed for the D-stem with a C+C pairing+ The folding is 8/5 in bacteria (E. coli and A. aeolicus), 9/4 in Archaea (M. jannaschii ) and Eukarya (X. laevis)+ The M. jannaschii tRNA Sec sequence was extracted from the TIGR mjdatabase (positions 111766-111855)+ The A. aeolicus tRNA Sec sequence was found at NCBI, accession number AE000720 (positions 8711-8809)+ The E. coli and X. laevis tRNAs Sec sequences were from Tormay et al+ (1994) and Sturchler et al+ (1993), respectively+ D+ It is frequently observed that N1-As (here N1-A63) react rapidly with DMS, even when base paired with a U, sometimes leading to the wrong interpretation that an A could be single stranded+ This reactivity is very likely due to the small size of the reagent and breathing of the helix, providing enough transient accessibility of the N1-A for the chemical to react+ However, in the gel provided in Figure 2A, it is obvious that N1-A63 is protected under native conditions, thus base paired to U51+…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier work (Sturchler et al+, 1993), the Xenopus laevis tRNA Sec molecule was monitored with a variety of enzymatic and chemical probes that led to a convergence of data in favor of the 9/4 model shown in Figure 1B+ The key point was to determine whether Figure 2A+ The presence of the modification is reflected on the gel by a pause of the reverse transcriptase one nucleotide prior to the modified base+ Again, one can see that C66 (pointed by the arrow in Fig+ 2A) is reactive to DMS only under semi-denaturing and denaturing conditions, showing the same reactivity as N3-C61 and N3-C62, which pair to G53 and G52, respectively, and N3-C68, which pairs to G5 (Fig+ 2A, lanes 4 and 6)+ To further strengthen the argument, we made use of lead acetate probing+ This chemical probe has been used with a variety of different RNAs by several authors as a singlestrand-specific probe (Brunel et al+, 1990;Hüttenhofer et al+, 1996;Walczak et al+, 1996)+ In addition, bulges in helices are exquisitely susceptible to this chemical (Hüt-tenhofer et al+, 1996), especially when flanked by two pyrimidines (Ciesiolka et al+, 1998), which is precisely the case in the tRNA Sec examined+ This molecule was submitted to lead acetate cleavage and no strong cleavages appeared in the C64/C66 area (Fig+ 2B)+ Cleavages were indeed observed between U67A and C62, but they are of an extremely low and evenly distributed intensity and, in addition, localized in the C64-C62 base paired region that should not be cut whether it is the 7/5 or 9/4 model (see Fig+ 1A and B for a summary of the cleavages)+ Therefore, these can be considered background cleavages+ Instead, a much stronger intensity of cuts should have been expected at the level of U66-C64 if C66 were bulged+ As anticipated, the T-loop was cleaved efficiently by Pb 2ϩ (Figs+ 1, 2B)+ These two experiments establish that C66 is not bulged, therefore strongly arguing in favor of the 9/4 model+ The tRNA Sec of the Archae M. jannaschii can only adopt the 9/4 folding Elucidation of the complete genomic sequence of the Archae M. jannaschii led the authors to the finding that the transcription and translation machineries in eukaryotes and this archae are very much alike (Bult et al+, 1996)+ When it comes to the tRNA Sec secondary structure of this organism, we found that the sequence constraints absolutely preclude a folding according to the 7/5 model, allowing only the 9/4 possibility (Fig+ 3)+ The complete similarity of the archaeal tRNA Sec secondary structure to that of eukaryotes cannot be taken as a fortuitous argument for two reasons+…”
Section: Chemical Probingmentioning
confidence: 94%
See 1 more Smart Citation
“…Phylogenetic distribution of the ATP-grasp enzymes suggests some interesting functional clues. Methanococcus jannaschii encodes two paralogous proteins that are both orthologous to RimK, yet there is no gene for Fraser et al (1995), Synechocystis sp.-from Kaneko et al (1996), M. jannaschii-from Bult et al (1996) A substantial number of enzymes that are similar in function to ATP-dependent carboxylate-amine ligases do not show any detectable sequence similarity to the ATP-grasp superfamily. These include such peptide synthetases as y-glutamyl-cysteine synthetase, eukaryotic GSHase, and bacterial peptidoglycan biosynthesis proteins Mu<, MurD, and MurE.…”
Section: R-co-0-rh-r-co-op03'-/'v R-co-s-coamentioning
confidence: 99%